PENGARUH BLANCHING TERHADAP PERUBAHAN NILAI NUTRISI MIKRO TEPUNG DAUN KELOR (Moringa oleifera) - Maria susana Medho; Endeyani V. Muhamad (Partner, 2019)
This research has been conducted in the Laboratory of Food Technology at the State Agricultural Polytechnic of Kupang, in March to September 2019. The purpose of this study is to examine the effect of blanching time on changes in the nutritional value of moringa leaf micronutrients. This study was designed using a Completely Randomized Design (CRD) with one factorial, namely the length of time Blanshing (B): B0 = without blanching; B1 = blanching 3 minutes; B2 = blanching 5 minutes and B3 = blanching 7 minutes. Each treatment was repeated 4 times to obtain 16 experimental units. Variables observed included Micro nutrients namely Vitamin C, Beta Carotene and Vitamin B2 Riboflavin and analyzed using HPLC. The results showed that blanching time greatly affected the decrease in micronutrients such as beta carotene, vitamin B2 and vitamin C. Vitamins C and  B2, beta carotene, of moringa leaf flour decreased with increasing blanching time. Vitamins C in moringa leaf flour without blanching is 94.98 mg / 100 g decreases after blanching 3 minutes to 33.63 mg / 100 g, and on blanching 5 minutes it becomes 9.64 g / 100 g and on blanching 7 minutes becomes 3 , 44 mg / 100 g. Vitamins B2 (riboflavin) Moringa leaf flour without blanching by 15.29 mg / 100 g decreases after blanching 3 minutes to 13.07 mg / 100 g, and on blanching 5 minutes becomes 13.49 mg / 100 g and on blanching 7 minutes to 8.68 mg / 100 g. Beta caroteness of Moringa leaf flour without blanching was 303.68 mg / kg decreased after blanching 3 minutes to 300.58 mg / kg, and on blanching 5 minutes it became 299.33 g / kg and in blanching 7 minutes it became 234.65 mg / kg. Moringa leaf flour without blanshing gives more smell of raw and not preferred when used as a fortifying material. The best time for blanching moringa leaves is 3 minutes because it can reduce smell of raw moringa and less decrease the value of micro-nutrients.